Combined large‐cell neuroendocrine carcinoma and endometrioid adenocarcinoma of the endometrium: A case report and survey of related literature. Issue 2 (February 2016) - Matsumoto, Harunobu; Nasu, Kaei; Kai, Kentaro; Nishida, Masakazu; Narahara, Hisashi; Nishida, Haruto
Abstract: Primary large‐cell neuroendocrine carcinoma of the endometrium is extremely rare and has a poor prognosis. This report describes a case of combined large‐cell neuroendocrine carcinoma and endometrioid adenocarcinoma of the endometrium diagnosed as stage IIIA. The patient underwent surgery and chemotherapy and has been well with no evidence of disease for 20 months. The optimal treatment for this rare tumor has not been established. Considering its rarity and variability, it is difficult to establish an evidence‐based therapeutic regimen.